Facile and convenient synthesis of (+/-)-Biotin via MgCl2/Et3N-mediated C-C coupling and mitsunobu reaction - Chavan, Subhash P.; Chavan, Prakash N.; Lasonkar, Pradeep B.; Khairnar, Lalit B.; Kadam, Appasaheb L. (Synlett, 2014)
A synthesis of (+/-)-biotin is described starting from simple starting materials viz. cyclohexanone and amino malonic acid ester. The key steps involved are MgCl2/Et3N coupling of amino malonic acid ester derivative and acid chloride, Mitsunobu reaction, ozonolysis, Staudinger reduction, novel urea formation, and subsequent dibenzylation. This approach is economical and involves high-yielding steps and simple reaction conditions.
Keywords: Appel reaction; biotin; Mitsunobu reaction; Ozonolysis; Staudinger reduction

Synthesis of 3-azidopiperidine skeleton employing ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether: total synthesis of d-2 receptor agonist (+/-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Lasonkar, Pradeep B.; Gonnade, Rajesh G. (Organic letters, 2018)
The total synthesis of (+/-)-quinagolide, which is a D-2 receptor agonist, was accomplished via a ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether route. Key features of the synthesis include Claisen rearrangement, PPTS (pyridinium p-toluene-sulfonate)-catalyzed one-pot acetal deprotection, followed by a diastereoselective Henry reaction, which enables construction of the required trans ring junction and CAN-mediated regioselective azidoalkoxylation of enol ether. The PPTS-catalyzed intramolecular diastereoselective Henry reaction to fix three contiguous stereocenters on tetrahydronaphthalene and the first-of-its-kind synthesis of the 3-azidopiperidine skeleton, using a CAN -mediated regioselective azidoalkoxylation of enol ether, are important findings of the present work.

Enantioselective formal total synthesis of (-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Organic Letters, 2019)
The enantioselective formal total synthesis of (-)-quinagolide has been accomplished in a linear sequence of 8 purification steps from pyridine. The key steps are (a) organocatalyzed Diets-Alder reaction for fixing all three stereocenters on piperidine ring; (b) protecting group enabled deoxygenation of isoquinuclidine skeleton under Birch reduction condition; (c) Lewis acid (TiCl4) catalyzed intramolecular Friedel-Crafts cyclization of dicarboxylic acid; and (d) one-pot diastereoselective ketone reduction-intramolecular cyclization to form oxazolidinone which enables trans-geometry installation. During the course of the synthesis, an interesting reductive cleavage of the C-N bond in the electron-deficient isoquinuclidine skeleton under the Birch reduction conditions has been observed. This is the first synthetic effort to access the core skeleton of (-)-quinagolide.

Total synthesis of (+/-)-quinagolide: a potent D-2 receptor agonist for the treatment of hyperprolactinemia - Chavan, Subhash P.; Kadam, Appasaheb L.; Kawale, Sanket A. (ACS Omega, 2019)
A potent dopamine (D-2) receptor agonist (+/-)-quinagolide, which is used for the treatment of hyperprolactinemia, was synthesized using the ring closing metathesis (RCM) approach from meta-hydroxybenzaldehyde as the starting material. The key features of this synthesis are pyrolytic elimination, late-stage expedient synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates from olefin 6, via conjugate addition-elimination upon acetate 11, followed by RCM and phenyliodine bis(trifluoroacetate) (PIFA)-mediated Hofmann rearrangement of piperidine-3-carboxamide, which enables the synthesis of 3-aminopiperidine skeleton of quinagolide. For the total synthesis of natural products such as ergot alkaloids, late-stage synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates using RCM and PIFA-mediated Hofmann rearrangement of piperidine-3-carboxamide, which allows quick access to the synthetically challenging 3-aminopiperidine skeleton, are the main achievements of the present work.

Furan-derived chiral bicycloaziridino lactone synthon: collective syntheses of oseltamivir phosphate (Tamiflu), (S)-pipecolic acid and its 3-hydroxy derivatives - Chavan, Subhash P.; Kadam, Appasaheb L.; Shinde, Shrikrishna S.; Gonnade, Rajesh G. (Chemistry-An Asian Journal, 2020)
A unified synthetic strategy for oseltamivir phosphate (tamiflu), (S)-pipecolic acid, and its 3-hydroxy derivatives from furan derived common chiral bicycloaziridino lactone synthon is described here. Key features are the short (4-steps), enantiopure, and decagram-scale synthesis of common chiral synthon from furan and its first-ever application in the total synthesis of biologically active compounds by taking the advantages of high functionalization ability of chiral synthon.
Keywords: Aziridine synthon; Chiral auxiliary; collective synthesis; Pipecolic acid; Tamiflu

Scalable synthesis of 3-Ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one: an important building block of the antidiabetic drug glimepiride - Chavan, Subhash P.; Pawar, Ambaji A.; Patil, Niteen B.; Kadam, Appasaheb L.; Shinde, Shrikrishna S. (Synthesis-Stuttgart, 2020)
A four-step, practical, and easily scalable synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one, an important building block of the antidiabetic drug glimepiride, has been accomplished. Key features are the synthesis of 3-methyl-4-hydroxy-2-butenolide in water and triflic acid mediated N-benzyl lactam N-deprotection. The main advantages of this process are the scalable synthetic route and decreased number of reaction steps, which paves the way for the industrial-scale synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one.
Keywords: antidiabetic drug; Butenolide; glimepiride; lactams; scalable synthesis

Formal synthesis of (-)-quinagolide: diastereoselective ring expansion via a bicyclic aziridinium ion strategy to access the octahydrobenzo[g]quinoline architecture - Chavan, Subhash P.; Kawale, Sanket A.; Pisal, Mahesh M.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2021)
The diastereoselective formal synthesis of (-)-quinagolide, a D-2 receptor agonist, has been achieved. The synthesis started from L-pyroglutamic acid and relied on utilization of (a) a stereospecific catalytic hydrogenation and diastereoselective Horner-Emmons-Michael cascade to obtain functionalized prolinate, (b) a Lewis acid mediated Pummerer cyclization to construct a tricyclic fused ring system, and (c) a diastereoselective ring expansion via a bicyclic aziridinium intermediate to access the required 3-substituted piperidine scaffold.

Revisiting classical pummerer cyclization reaction: a key strategy for the synthesis of (+/-)-quinagolide - Chavan, Subhash P.; Kawale, Sanket A.; Tripathi, Anupam; Kadam, Appasaheb L.; Gonnade, Rajesh G. (ChemistrySelect, 2022)
A formal synthesis of (+/-)-quinagolide using beta-alanine as a starting material has been achieved. Late stage intramolecular classical Pummerer reaction has been used as a key synthetic tool to construct octahydrobenzo[g]quinoline skeleton of quinagolide. Conjugative reduction of olefin, regioselective C-alkylation over O-alkylation of beta-ketoester followed by retro-Dieckmann/ Dieckmann reaction sequence has been used as a key reaction sequence to achieve prerequisite sulfoxide for the Pummerer reaction. While revisiting the classical Pummerer reaction, the one-pot sequential thionium ion induced cyclocarbamation followed by N-carbamate deprotection and Friedel-Crafts type Pummerer cyclization was observed as an important finding of the present work.
Keywords: Alkylation; Cyclocarbamation; Hyperprolactinemia; rearrangement; Thionium ion